Analisis SWOT dalam Strategi Pemasaran Produk Perbankan Syariah di Indonesia - Ricki Febrian Syah; Muhammad Iqbal Fasa; Suharto Suharto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
Marketing strategy is a procedure in marketing that is planned and arranged to be carried out in order to achieve company goals. As various banking institutions or companies develop, competition between companies is inevitable. Therefore, to face these competitions, a company requires a process of understanding the internal situation of the company itself and the external environment in which the company will compete. This study aims to find out how Islamic banks determine the direction of what strategy to do in the present and in the future using a SWOT analysis. The method used in this writing is qualitative in which the approach used is a descriptive approach. The results of the discussion show that Islamic banks are able to dare to compete in a competitive competitive market, strengthen cooperation with cooperatives, improve relationships with scholars, government and entrepreneurs, increase customer loyalty, and improve product quality, and increase promotion through various media and establish marketing strategies effective and efficient.